Corporate responsibility in the history of criminal law reform and victimology in Indonesia - Saogo, Marhel (Institute Of computer Science (IOCS), 2025)
In Indonesia, corporations play a crucial role in achieving national prosperity, especially in the context of globalization. This study examines two main issues: (1) the system of Corporate Criminal Liability and the implementation of sanctions to protect victims of corporate crime, and (2) corporate accountability within the reform of criminal law in Indonesia. Utilizing a normative juridical approach, the research explores statutory, conceptual, and case-based frameworks. Key findings from various court decisions highlight that corporations often face mere fines for their criminal activities, such as those documented in several district court rulings and decisions of the Supreme Court. The study concludes that while the corporate criminal liability system in Indonesia is evolving, it holds the potential to enhance law enforcement effectiveness against corporate crime. Currently, corporations can be prosecuted for economic, environmental, and corruption crimes, but enforcement focuses primarily on fines and revocation of business licenses. Significant legislative advancements, particularly Law Number 1 of 2023, recognize legal entities as valid subjects of criminal liability. The study recommends applying a principle of prudence in the examination and prosecution of corporate cases to improve accountability and prevent future offenses.